Contesting Land and Custom in Ghana. State, Chief and the Citizen - S. Amanor, Kojo (Law, Governance, and Development, 2008)
The contributions to this essential volume critically examine ideas on customary land tenure in Ghana. They analyse the relations between the customary and statutory tenure and the institutional interactions between the state and traditional authorities in land administration, addressing issues of power, economic interests, transparency, accountability, conflicts and notions of social justice, equity and negotiation. They examine both past and contemporary policy issues, and present a number of case studies with implications for the integration of customary institutions into the framework of state land administration.